"SYMBIOTIC" HEMOFILTRATION FOR CHRONIC RENAL F AILURE COMPENSATION - E. A. Yumatov; O. S. Glazachev; E. N. Dudnik; S. S. Pertsov; V. V. Raevskiy (Исследования и практика в медицине)
AbstractWidely used nowadays hemodialysis and hemofiltration cannot replace completely the excretory function of human kidneys in the natural conditions of physiological regulation. The aim of our study is to develop and create a new method and apparatus for CRF patients «symbiotic» compensation, based on hemofiltration and healthy humans kidneys natural physiological functions, excluding mixing of partners blood.Method of «symbiotic» hemofiltration is based on mutual exchange of equivalent blood ultrafiltrate volumes between healthy person and CRF patient, needed to be cleansed from metabolites. During exchange procedure patient’s and a healthy person’s circulations are separated by hemofilters excluding blood mixing.During CRF patient’s blood cleansing from metabolic products separate hemofiltration of healthy donor and CRF patient in equal volumes is processed. Patient’s blood ultrafiltrate enters the bloodstream of a healthy person, as a healthy person ultrafiltrate in the same extent enters the bloodstream of CRF patient. At the same time remaining after filtration blood components of donor and patient are returned in their bloodstream respectively.Fundamentally important advantage of «symbiotic» hemofiltration is that CRF patient’s blood is cleansed from uremic metabolites due to healthy human kidneys natural physiological functions. «Symbiotic» hemofiltration is a highly effective physiological method of CRP patient’s blood purification from the uremic substances.